STRATEGI PENGEMBANGAN AGROPOLITAN KOPI ROBUSTA BERSERTIFIKAT INDIKASI GEOGRAFIS DI KECAMATAN PUPUAN TABANAN - Ni Made Citra Laksmi; I Ketut Sumantra; Wayan Maba (MediaTrend, 2021)
The high demand for Pupuan robusta coffee was not followed by an increase in production. Robusta coffee farming has not been able to increase farmers' income, therefore the concept of agropolitan area development is needed. The purpose of this study was to formulate a strategy for developing agropolitan areas for robusta coffee in Pupuan, research time from September to November 2020. The research method uses are observation, interviews, and questionnaires. The data analysis used in this study are SWOT and QSP matrix. The results showed that the results of IFAS and EFAS data processing, the values of x = 1.13 and y = 1.24 are obtained that they are in quadrant I (Growth), so the strategy applied is the SO strategy. Based on the QSPM calculation, the highest TAS value was 6.96. The conclusion from the research results shows that in the Pupuan sub-district there is a potential for upstream and downstream Robusta coffee agribusiness. The strategy obtained in accordance with the SWOT table is the SO strategy. An alternative strategy in accordance with QSPM is to carry out an applied study of the pre-harvest and post-harvest processing technology for robusta coffee.